(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The purpose of the study is to assess the functional state of students of one age group (18-20 years old, n=135) for 2 years (2023, 2024, 1st and 2nd year, respectively) during an active educational process based on the analysis of heart rate variability parameters. Students underwent an electrocardiographic (ECG) examination using the Varicard 2.52 software and hardware complex. Research has shown that 40.5% of girls out of 97 surveyed and 35.6% of boys out of 38 people have a state of tension in their regulatory systems.